Personal reflections on a tale of two books: social and environmental accounting research in the past, present and future - Reg Mathews (Australasian Accounting, Business and Finance Journal, 2008)
This paper was requested by the guest editors of the Australasian Accounting, Business and Finance Journal (AABFJ) following the Sydney CSEAR conference. One topic suggested to me was to write a comment on recent developments leveraging on GG 2007 or that part that has not been published previously. I am pleased to attempt this but wish also to make reference to another book published at the same time (Unerman, Bebbington and O’Dwyer (UBOD 2007), because I believe that the different perspectives presented are informative for all scholars in the field of SEAR which is now often referred to as SA. The remainder of this paper other than the introduction and conclusion will consist of firstly a review of GG 2007, secondly a review of UBOD 2007, and thirdly a number of observations based on these contrasting works.
Keywords: Sustainable Development; Gray and Guthrie 2007; Unerman Bebbington and O& #x27; Dwyer 2007; Social and Environmental Accounting; Review